Value of sonographic anterior‐posterior renal pelvis measurements before and after voiding for predicting vesicoureteral reflux in children. Issue 8 (25th December 2014) - Demir, Senay; Tokmak, Naime; Cengiz, Nurcan; Noyan, Aytul
ABSTRACT Purpose Voiding cystourethrography (VCUG) is the gold standard for diagnosing vesicoureteral reflux (VUR), but it is important to minimize the use of VCUG because of the urinary catheterization and radiation exposure required. Ultrasound (US) observations suggest that pelvicalyceal dilatation varies according to the degree of bladder fullness in children with urinary tract infection. The aim of this study was to assess whether anterior‐posterior (AP) measurements of the renal pelvis on US before and after voiding can be used as a screening tool while predicting the presence of VUR in children. Methods The subjects were toilet‐trained children older than 4 years who required VCUG. Two groups were established based on the VCUG results: a VUR group of 40 kidney units (each unit defined as calyces and ureter) that exhibited different severities of reflux, and a control group of 68 kidney units unaffected by VUR. Prior to VCUG, US AP measurements of the renal pelvis of each kidney unit were recorded when the urinary bladder was full and again after bladder emptying. The change in AP measurement from before to after voiding was compared between the two groups. Results The mean change in AP measurements from before to after voiding in the VUR group was significantly greater than that in the control group (p = 0.003). Conclusions Comparing US AP measurements of the renal pelvis before and after voiding is useful for identifying children who are suspected to have VUR and thus require immediate VCUG. © 2014 Wiley Periodicals, Inc. J Clin Ultrasound 43:490–494 2015